The design of a single seater helicopter fuselage [compact disc] - 208047 Sharmanrizal Rustam (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Aeronautik)) - Universiti Teknologi Malaysia, 2006